Ustekinumab in the therapy of chronic plaque psoriasis - Jenna L O’Neill; Robert E Kalb (Biologics: Targets & Therapy, 2009)
Jenna L O’Neill, Robert E KalbState University of New York at Buffalo, School of Medicine and Biomedical Sciences, Department of Dermatology, NY, USAAbstract: Psoriasis is a chronic inflammatory disorder characterized by T cell dysregulation and a chronic inflammatory infiltrate within the epidermis. Several cytokines play an important role in the pathogenesis of psoriasis, including interleukin-12 (IL-12) and IL-23. These cytokines act via induction of pro-inflammatory cytokines which promote chronic inflammation and auto-reactivity. Ustekinumab is a fully human monoclonal antibody against the common p40 subunit of IL-12 and IL-23. Two randomized, double-blind, placebo-controlled trials of ustekinumab have demonstrated significant and prolonged efficacy in the treatment of plaque psoriasis. Adverse events were generally similar across treatment and control groups. Studies are ongoing to assess the long term safety and efficacy profiles of ustekinumab.Keywords: ustekinumab, psoriasis, plaque